Evaluation Of Serum Phosphorus Levels And Obesity - John Sim; Ning Smith; Joanie Chung; Kamyar Kalantar-Zadeh (The Korean Society of Nephrology, 2012)
Higher dairy intake overall has been associated with lower risk for the metabolic syndrome while higher phosphorus (phos) intake has conversely shown greater risk for obesity and the metabolic syndrome. The higher phos content in food preservatives and food flavorings and the greater phos absorption from consumption of animal products overall contribute to the poor dietary habits linked with the rising rate of obesity in the USA. We sought to determine whether higher levels of serum phos are associated with obesity within a large ethnically diverse population of patients who are free of kidney disease. In the period 1/1/2007-12/31/2011, all subjects age>17yrs with measured serum phos, documented eGFR>60ml/min, and documented body mass index (BMI) were identified from the Kaiser Permanente So Cal healthplan. Subjects were categorized into population based quartiles from phos values. Obesity was defined as BMI>25. Race/ethnicity, HTN, and DM were extracted from electronic medical records and the use of ICD codes. A total of 88,094 subjects were analyzed. In the univariate regressions, higher phos quartiles compared to the lowest quartile, had OR (95% CI) for obesity of 1.09(1.06-1.12), 1.06(1.03-1.08), and 1.05(1.02-1.07) respectively for phos quartiles 3.1-3.4(mg/dl), 3.5-3.9, 4.0-5.7 vs 1.9-3.0. Linear regressions showed every 0.5mg/dl phos increase demonstrated OR of 1.02 (1.01-1.02) for obesity. These differences were not sustained in the multivariable analyses. However, Blacks (1.29) and Hispanics (1.48) had higher risk for obesity while risk for Asians (0.38) were lower compared to whites (p<0.05). Presence of DM (2.00) and HTN (2.16) also had higher OR for obesity. In subjects without kidney disease, serum phos levels may be reflective of poor dietary habits and may represent a risk factor for the metabolic syndrome.